Strategic airlift operationalizing constructive simulations - Barwell, R. (Rob); Wainer, G.A. (Gabriel) (2020)
Large organizations now use Modeling and Simulation (M&S) for complex systems. This evolution has also resulted in a lack of simple tools and processes to define models and experiments which hinders wide scale user adoption of M&S to solve many real-world problems. By exploring the Arctic logistical support base problem, we will illustrate how a simple M&S process and system can be used by operators with limited knowledge of M&S. This will be demonstrated by determining a temporary logistical support base for re-supplying military operations in the Canadian Arctic.